The Effect of Additional Ameliorants on The Growth of Agarwood, Jackfruit, and Durian Seedlings in Former Gold Mining Land - Afratullah, Afratullah; Aji, Irwan Mahakam Lesmono; Shabrina, Hasyyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Post-gold mining soils generally exhibit low fertility, acidic pH, and limited nutrient availability, which constrain plant growth and revegetation efforts. This study aimed to evaluate the interaction effect of compost and dolomite ameliorants on the growth of gaharu (Gyrinops verstegii), jackfruit (Artocarpus heterophyllus), and durian (Durio zibethinus) seedlings cultivated on post-gold mining soil. The experiment was conducted in a greenhouse using a Completely Randomized Design (CRD) with a factorial arrangement consisting of two factors: ameliorant treatments (without ameliorant, 50 g compost + 50 g dolomite, and 60 g compost + 40 g dolomite) and plant species (gaharu, jackfruit, and durian). Each treatment combination was replicated three times, resulting in 27 experimental units. Growth parameters observed included plant height, stem diameter, leaf number, root length, fresh biomass weight, and dry biomass weight. Data were analyzed using Analysis of Variance (ANOVA) followed by the Honestly Significant Difference (HSD) test at the 5% significance level. The results showed that the interaction between ameliorants and plant species significantly affected stem diameter, leaf number, and fresh biomass weight, but had no significant effect on plant height, root length, and dry biomass weight. The best growth performance was generally obtained from the application of 60 g compost and 40 g dolomite. Therefore, compost and dolomite can be recommended as effective soil ameliorants to support revegetation programs on post-gold mining lands using forestry and multipurpose tree species.